A new autosomal recessive anomaly mimicking Fanconi's anaemia phenotype. Issue 1 (January 1993) - Milner, R D; Khallouf, K A; Gibson, R; Hajianpour, A; Mathew, C G
Abstract : A family in which three siblings born to related parents all manifested clinical abnormalities characteristic of Fanconi's anaemia (microcephaly, short stature, slow growth, beak nose, micrognathia, skin dyspigmentation and forearm and thumb dysplasia in 2/3) is reported. All five family members had normal spontaneous chromosome breakage, a normal response to diepoxybutane and mitomycin C, and were fully informative for linkage with four DNA markers from chromosome 20q12-13.3 with no evidence for linkage. It is concluded that abnormalities typical for Fanconi's anaemia are inherited as an autosomal recessive without the defect responsible for increased chromosomal fragility and independently from the genes so far identified as being responsible for Fanconi's anaemia.